Analysis of the Associations between Vitamin D and Albuminuria or β-Cell Function in Chinese Type 2 Diabetes - Cai, Xiaoling (Hindawi Publishing Corporation, 2014)
Objective. To investigate the associations of 25-(OH)D and β-cell function or insulin resistance or albuminuria in Chinese type 2 diabetic patients. Methods. In total, 1408 type 2 diabetic patients without vitamin D supplement were included in this retrospective study. Results. Comparison between patients with and without 25-(OH)D deficiency indicated that, compared with patients with 25-(OH)D ≥ 50 nmol/L, patients with 25-(OH)D < 50 nmol/L showed a higher level of urine albumin-creatinine ratio (ACR) (90.15 ± 10.30 mg/g versus 52.79 ± 14.97 mg/g). Multiple regression analysis indicated that 25-(OH)D was independently and negatively correlated with urine ACR (OR = 0.985, 95%CI 0.972–0.999, P = 0.03), adjusted by age, diabetic duration, HBP duration, SBP, HbA1c, creatinine, LDL-C, triglyceride, total cholesterol, and HDL-C. Compared with patients with normal level of urine ACR, patients with higher level of urine ACR showed a significant lower level of 25-(OH)D (34.49 ± 13.52 nmol/L versus 37.46 ± 13.6 nmol/L, P = 0.00). Analysis of the associations of 25-(OH)D and β-cell function or insulin resistance showed that 25-(OH)D may not correlate with β-cell function or insulin resistance. Conclusion. 25-(OH)D was independently associated with albuminuria in Chinese type 2 diabetic patients but was not associated with β-cell function or insulin resistance.